Pengaruh Kualitas Layanan Digital dan Konvensional terhadap Kepuasan Nasabah BRI - Ade Herlan; Andre Suryaningprang; Dadan Abdul Aziz Mubarok; Ezra Karamang (CV. ITTC INDONESIA, 2026)
The development of digital transformation in the banking industry requires every financial institution to continuously improve service quality in order to maintain and increase customer satisfaction. This is also the case at Bank Rakyat Indonesia Panjalu Unit, which faces challenges in the form of customer complaints regarding long queues for conventional services and technical obstacles in the BRImo application, such as system disruptions and errors during transactions. This situation shows a gap between customer expectations and the reality of the services they receive, necessitating research to identify the factors that influence their satisfaction. This study aims to analyze the effect of digital and conventional service quality on customer satisfaction and to determine the most dominant influencing variables. The method used is a quantitative approach with an associative research design. The research sample consisted of 100 respondents selected through simple random sampling from a total of 8,753 active customers. Data were collected using a Likert scale questionnaire, interviews, and literature studies, then analyzed using multiple linear regression through validity, reliability, classical assumption tests, t-tests, and F-tests using SPSS. The results show that digital services have a significant negative effect on customer satisfaction (sig. 0.024), while conventional services have a positive and significant effect (sig. 0.000) and are the most dominant variable. Simultaneously, both variables contribute 73.8% to customer satisfaction, so improving the stability of digital systems and enhancing the quality of face-to-face interactions are strategic steps to increase customer loyalty and trust.